Spontaneous Carotid Cavernous Sinus Fistula Disappeared Following Embolization, Ligation of External Carotid Artery and Irradiation - ENKAKU, Fumihide; ISHIKURA, Akira; IKEDA, Masato (Japanese Journal of National Medical Services, 1988)
A 62-year-old female with carotid cavernous sinus fistula (CCF) complained of exophthalmos, periorbital edema, chemosis, diplopia, blephaloptosis and bruits. Cerebral angiography demonstrated mixed typed CCF fed by external and internal carotid arteries. Embolization and ligation of external carotid artery and liniac irradiation to the region of fistula were started. Symptoms and signs gradually improved. In the management of spontaneous CCF, these therapeutic modalities were considered one of the effective methods in cases of low flow, low pressure dural fistulas, in surgically inaccessible ones, or in poor risk patients.